Growth and structural properties of step-graded, high Sn content GeSn layers on Ge. (24th August 2017) - Aubin, J; Hartmann, J M; Gassenq, A; Rouviere, J L; Robin, E; Delaye, V; Cooper, D; Mollard, N; Reboud, V; Calvo, V
Abstract: Two approaches have been compared for the low temperature epitaxy of thick, partially relaxed GeSn layers on top of Ge strain relaxed buffers. The benefit of using step-graded instead of constant composition layers when targeting really high Sn contents (16%, here) was conclusively demonstrated. Digermane (Ge2 H6 ) and tin-tetrachloride (SnCl4 ) were used as Ge and Sn precursors, respectively. The growth pressure (100 Torr) and the F(Ge2 H6 )/F(SnCl4 ) mass-flow ratio being constant, it was through a temperature lowering that the Sn concentration in the graded structure was increased. X-ray diffraction, atomic force microscopy and transmission electron microscopy were used to gain access to the Sn concentration, the strain state, the surface morphology and thicknesses of the heterostructures. Using a step-graded approach allowed us to gradually relax the strain in the GeSn layers. It helped us obtain high crystalline quality and avoid Sn segregation/precipitation for high Sn contents.